CODE-SWITCHING AND CODE-MIXING IN FAN LETTERS OF INDONESIAN BANGTAN SONYEONDAN (BTS) FANS ON THE WEVERSE APP - Ghina, Ghina (JURNAL KONFIKS, 2025)
This research is motivated by the phenomenon of language use in fan letters written by BTS fans on the Weverse application, which shows the occurrence of code-switching and code-mixing as a form of linguistic creativity in global digital communication. This study aims to describe the types of code-switching and code-mixing that appear, analyze the factors that cause both phenomena, and explain their implications for Indonesian language learning in personal and official letter materials. This research uses a qualitative approach with a descriptive method. The data are written utterances from fan letters of Indonesian BTS fans on the BTS group channel in the Weverse application, collected through observation and note-taking techniques. The data were analyzed through the stages of reduction, presentation, and conclusion-drawing, and validated using theory triangulation. The results show that there are 271 instances of code-switching, all of which are external code-switching. In addition, 511 instances of code-mixing were found, consisting of inner code mixing, outer code mixing, and hybrid code mixing. The dominant factor causing code-switching is the interlocutor, while the main factor causing code-mixing is the speaker. These findings indicate that fans use language variation as a strategy to adapt to global communication contexts as well as to strengthen social identity within the fandom community. Pedagogically, the results of this study are relevant to Indonesian language learning, especially in teaching personal and official letter writing. The analysis of code-switching and code-mixing can serve as contextual teaching material to enhance language awareness, understanding of language varieties, and students’ functional writing skills in diverse communication situations.